Left Out of the Bargain : Settlements in Foreign Bribery Cases and Implications for Asset Recovery - Oduor, Jacinta Anyango (Washington, DC: World Bank, 2013)
Over the past decade, countries have increasingly used settlements—that is, any procedure short of a full trial—to conclude foreign bribery cases and have imposed billions in monetary sanctions. There exists a gap in knowledge, however, regarding settlement practices around the world and the disposition of these monetary sanctions—notably through the lens of recovery of stolen assets. Left Out of the Bargain , a study by the Stolen Asset RecoveryInitiative (StAR), provides an overview of settlement practices by civil and common law countries that have been active in the fight against foreign bribery.